Development of sex pheromone traps for monitoring the legume podborer, Maruca vitrata (F.) (Lepidoptera: pyralidae) - Downham, M.C.A.; Tamo, Manuele; Hall, D.; Datinon, B.; Dahounto, D.; Adetonah, J. (2002)
The Natural Resources Institute (NRI) and the International Institute of Tropical Agriculture (IITA) are collaborating to develop sex pheromone traps as monitoring tools for Maruca vitrata. The principal component of the pheromone is (E, E)-10, 12-hexadecadienal. Our trapping experiments in cowpea fields in Benin have shown that the optimal synthetic blend also contains small amounts of (E, E)-10, 12-hexadecadien-1-ol and (E)-10-hexadecenal. Polyethylene vial lures containing 0.1 mg of pheromone attracted more males than other combinations of dose or dispenser. Lures showed no loss of effectiveness for up to four weeks in the field. A water-trap made from a plastic jerry can was superior to commercial funnel- and sticky-trap designs and 120 cm was the optimum height for traps. Females comprised up to 50% of total catches with synthetic lures, though almost none were attracted to traps baited with live females. Preliminary observations indicated a temporal coincidence between catches in traps placed outside cowpea fields and the appearance of larvae in fields a few days later. Thus pheromone trap catches may predict larval infestations.